Mobile multicast in hierarchical proxy mobile IPV6 - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Mustafa, Amin; Abdullah, Khaizuran (IOP Publishing, 2013)
Mobile Internet Protocol Version 6 (MIPv6) environments have been developing very rapidly. Many challenges arise with the fast progress of MIPv6 technologies and its environment. Therefore the importance of improving the existing architecture and operations increases. One of the many challenges which need to be addressed is the need for performance improvement to support mobile multicast. Numerous approaches have been proposed to improve mobile multicast performance. This includes Context Transfer Protocol (CXTP), Hierarchical Mobile IPv6 (HMIPv6), Fast Mobile IPv6 (FMIPv6) and Proxy Mobile IPv6 (PMIPv6). This document describes multicast context transfer in hierarchical proxy mobile IPv6 (H-PMIPv6) to provide better multicasting performance in PMIPv6 domain.